The Equivalence Problem in the Parallel Dictionaries of the 17th Century - Judžentytė-Šinkūnienė, Gintarė; Zubaitienė, Vilma (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English] This paper deals with the parallel dictionaries of the 17th century Minor Lithuania, the Grand Duchy of Lithuania and Latvia: the anonymous manuscript Lexicon Lithuanicum (late 17th century) and Georg Mancelis’s Lettus (1638) as well as Konstantinas Sirvydas’s Dictionarium trium lingvarum (1642) and Georg Elger’s Dictionarium Polono-Latino-Lottauicum (1683). Two bilingual German-Lithuanian resp. Latvian language and two trilingual Polish-Latin-Lithuanian resp. Latvian language dictionaries were chosen for the research. The aim of this study is to investigate the equivalence of Lithuanian and Latvian correspondences in the parallel dictionaries of the 17th century, i.e., to reveal how the meaning of the headword (compound word) is reflected in each different language. In order to achieve this aim, the paper identifies what kinds of equivalents (derivatives, adapted loanwords, periphery) are chosen – in other words, the attention is drawn to the formal expression of equivalence. If the number of equivalents is increased, the systematic relations among them are investigated (loanword – native word, neologism – descriptive compound, several synonyms etc.). Next, the types of equivalents are defined according to their revealed semantic content: the equivalents corresponding or partially corresponding to the meaning as well as the equivalents that only explain the concept expressed by the word of the main language. The semantic content of the equivalents is analyzed based on thematic groups: (a) the names of persons; (b) the names of things; (c) the names of animals and plants; (d) place names; (e) names for a specific period of time; (f) food names; (g) the names of diseases. Later on, the influence of the headwords (German, Polish) on the correspondences of Lithuanian and Latvian is studied. The following step is to analyze the similarities and differences between the Lithuanian and Latvian equivalents in the parallel dictionaries when the same headwords or phrases are translated from German and Polish. It is quite clear that both the established loanwords and neologisms are chosen as equivalents in the researched dictionaries. Once the loanword has become established, it is taken as an equivalent and is regarded as the most relevant indicator of meaning. When a new reality and its translation are not known, a neologism is being created, the synonyms of the wider meaning are given or the meaning is described in a descriptive way. Foreign realities are often translated in a descriptive way by distinguishing an important semantic attribute. Lexicographers perceived the multiplicity of word meaning but did not always provide formal indicators.